Acute Imidacloprid Poisoning in Thailand - Sriapha C; Trakulsrichai S; Tongpoo A; Pradoo A; Rittilert P; Wananukul W (Dove Medical Press, 2020)
Charuwan Sriapha,1 Satariya Trakulsrichai,1,2 Achara Tongpoo,1 Aimon Pradoo,1 Panee Rittilert,1 Winai Wananukul1,3 1Ramathibodi Poison Center, Faculty of Medicine Ramathibodi Hospital, Mahidol University, Bangkok 10400, Thailand; 2Department of Emergency Medicine, Faculty of Medicine Ramathibodi Hospital, Mahidol University, Bangkok 1400, Thailand; 3Division of Clinical Pharmacology and Toxicology, Department of Medicine, Faculty of Medicine Ramathibodi Hospital, Mahidol University, Bangkok 1400, ThailandCorrespondence: Satariya TrakulsrichaiRamathibodi Poison Center, Faculty of Medicine Ramathibodi Hospital, Mahidol University, Bangkok 10400, ThailandTel +66-2-2011084Fax +66-2-2011086Email satariya.tra@mahidol.ac.thIntroduction: Imidacloprid is the most commonly used neonicotinoid insecticide worldwide. Despite its reputation for safety, there is increasing evidence regarding its toxicity. This study characterized the clinical manifestations and outcomes of acute imidacloprid poisoning.Methods: This was a retrospective study of patients with imidacloprid poisoning who were referred to the Ramathibodi Poison Center in Bangkok, Thailand between 2010 and 2018.Results: A total of 163 patients with imidacloprid-only exposure were included. Most were exposed by ingestion (93.3%). The patients were predominantly male (55.8%), with a median age of 41.3 years. The common presenting features were gastrointestinal symptoms (63.8%) with no corrosive injuries and neurological effects (14.2%). The majority of medical outcomes was no (18.4%) to mild (76.1%) toxicity. One patient had symptoms mimicking cholinergic syndrome, three developed liver injury, and five died. Among the five deaths, two patients presented severe initial severity, and one presented moderate initial severity. Two of the patients who died initially presented only mild severity. The mortality rate was 3.1%. The estimated amount of ingestion, cardiovascular effects (especially tachycardia and cardiac arrest), central nervous system effects (especially coma), dyspnea, and diaphoresis were significantly associated with mortality. Patient management primarily included supportive and symptomatic care.Conclusion: Most patients with imidacloprid poisoning developed only mild toxicity. The mortality rate was low, but a few patients with mild initial severity died. Patients who ingest a large amount or show these warning signs including cardiovascular effects, central nervous system effects, dyspnea, and diaphoresis at the initial presentation should be considered for close observation and monitoring.Keywords: imidacloprid, neonicotinoid insecticide, poisoning, toxicity, humans